Pemberdayaan UMKM dan Literasi Keuangan melalui Digitalisasi dan Budaya Menabung di Desa Raya Dusun IV Berastagi - Nur Anisah Hrp; Nur Hapijah Sihombing; Khoirun Rizky; Ine Tasya; Rosliana Hrp (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
The Community Service Program (KKN) implemented in Raya Village, Dusun IV, Berastagi, focused on community economic development through integrated work programs initiated by the Faculty of Economics. These programs included mentoring Micro, Small, and Medium Enterprises (MSMEs), implementing the “Gambling to Save” initiative to promote financial literacy, and facilitating MSME registration on Google Maps as a digital marketing strategy. These activities aimed to empower the local community by improving product innovation, strengthening entrepreneurial skills, enhancing financial management capabilities, and expanding the marketing reach of high-value MSMEs. The methodology employed consisted of structured financial management training to encourage a sustainable saving culture, continuous business management mentoring, and promotional optimization through Google Maps registration and digital presence management. As a result, MSME actors gained better visibility, accessibility, and competitiveness in broader markets. Additionally, the program successfully increased community awareness of local economic potential as a sustainable resource that can support long-term economic resilience and inclusive rural development.